MEMETAKAN LEARNING AGILITY PADA PERUSAHAAN SWASTA DI DKI JAYA: APAKAH ONLINE LEARNING, GRIT, DAN COLLABORATIVE SKILL CUKUP BERDAMPAK? - Lovis Ardiyanto; Richkho Efendi; Winson Yoe; Nopriadi Saputra (JEBIM Prima, 2022)
The research explored the description of learning agility and the effect of each independent variable, namely online learning, grit, and collaborative skill on learning agility of millennial employees in DKI Jaya. This quantitative research applied an associative approach with data collected through questionnaires with a total of 387 millennial employees in DKI Jaya. This research suggested that millennial employees in DKI Jaya performed good learning agility, online learning, grit, and collaborative skill. Using simple regression analysis, it was known that online learning and collaborative skill each had significant effect on learning agility, while grit was found not to have significant effect on learning agility of millennial employees in DKI Jaya. By this research, the institutions were supposed to continuously support the development of learning agility, online learning, grit, and collaborative skill of millennial employees in DKI Jaya for the sustainability of the institutions.